Waste to wealth UV LED acrylated curable coating: a waste palm cooking oil innovation - Onn, Munirah; Wahit, Mat Uzir; Mazni, Mazleenda; Zainudin, Aznilinda (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This study introduces a UV-curable coating derived from acrylated waste palm cooking oil (AWPCO), transforming a common environmental pollutant into a high-value, sustainable material. Waste palm cooking oil (WPCO), if improperly disposed of, causes significant environmental damage. To address this, WPCO was modified using Cis–9–octadecenoic acid and enzymatic catalysis to enhance double bonds, enabling acrylation and UV crosslinking. The resulting AWPCO was blended with reactive monomers and cured using UV LED technology, a green and energy-efficient method that reduces power consumption and volatile organic compound (VOC) emissions. The optimized coating, particularly with Trimethylolpropane triacrylate (TMPTA) and a cationic photoinitiator, demonstrated exceptional properties, including high gel content (88.90%), improved hydrophobicity (contact angle 86°), and enhanced solvent resistance. The use of UV LED curing ensures faster processing, lower costs, and environmental friendliness, making this technology highly competitive. This innovation offers a “waste-to-wealth” solution with significant socio-environmental impact by reducing pollution and promoting sustainability. Its commercial potential is substantial, catering to industries seeking eco-friendly, high-performance coatings, and aligning with global green technology trends. AWPCO-based coatings provide a scalable, cost-effective alternative to conventional materials, driving a positive shift toward circular economic practices